2018
DOI: 10.1021/acs.biomac.7b01765
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Functionalized Fiber Yarns Spun from Deep Eutectic Cellulose Solutions for Nonspecific Hormone Capture in Aqueous Matrices

Abstract: A wood based yarn platform for capturing pharmaceutical molecules from water was developed. Cellulose fiber yarns were modified with cyclodextrins, and the capture of 17α-ethinyl estradiol (EE2), a synthetic estrogen hormone used as contraceptive, from water was tested. The yarns were prepared by spinning a deep eutectic solution (DES) of cellulose in choline chloride-urea. Despite their high porosity and water sorption capacity (5 g/g), the spun fiber yarns displayed high wet strength, up to 60% of that recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
(117 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, these filaments absorb significantly more water than a fiber yarn spun from macroscopic cellulose fibers (5 g/g), 16 or even fluff pulp (12 g/g), 48 which is a typical component in commercial absorbent products. This highlights the benefits of the increased surface area by disintegration of wood fibers to the nanoscale.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these filaments absorb significantly more water than a fiber yarn spun from macroscopic cellulose fibers (5 g/g), 16 or even fluff pulp (12 g/g), 48 which is a typical component in commercial absorbent products. This highlights the benefits of the increased surface area by disintegration of wood fibers to the nanoscale.…”
Section: Resultsmentioning
confidence: 99%
“…Following this new development, Wang et al and Mendonça et al published the first studies on the use of different DES as ligand [77], as 100% solvent for SARA ATPR [78] or both [77]. Other studies also reported the use of DES as solvent medium for polymer synthesis [46,79,80,81,82,83,84,85,86,87,88,89,90]. In particular, the communication of Park and Lee on the polymerization of 3-octylthiophene in DES presented interesting features regarding the use of DES as a solvent in polymerization.…”
Section: Polymeric Synthesis Using Desmentioning
confidence: 99%
“…Given the range of attainable properties, the yarns can be further developed in an application-oriented approach. For example, Orelma et al 43 produced fiber yarns with a similar process. The open inner structure and good water absorption capability of the fiber yarns enabled their use in cyclodextrin-based capture of synthetic estrogen hormones from water.…”
Section: Resultsmentioning
confidence: 99%